Study of Electrical Energy Consumption and Potential Saving in Malaysia Commercial Kitchen - Abu Hasan, Muhammad Adam; Noranai, Zamri (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The commercial kitchen sector in Malaysia, a cornerstone of the nation’s vibrant culinary landscape, is experiencing significant growth driven by economic development and urbanization. This expansion is accompanied by a substantial increase in electrical energy consumption, posing challenges related to rising operational costs and environmental sustainability. This study investigates the patterns of electrical energy usage in Malaysian commercial kitchens, identifies potential energy-saving, and analyzes the associated cost-saving benefits. The research aims to highlight the importance of optimizing energy consumption in commercial kitchens. By analyses the current consumption patterns, assessing the efficiency of major appliances, and exploring behavioural and procedural changes, the study provides actionable insights for enhancing energy efficiency.